Implementing the Five-Fold Ministry in Kumi Hospital Parish, Diocese of Kumi - Simon Akemo (Uganda Christian University, 2024)
This thesis delves into the implementation of the five-fold ministries (apostles, prophets, evangelists, pastors, and teachers) as outlined in Ephesians 4:11-16 within the context of the Christian faith. Each ministry role is examined in detail, from the historical significance of apostles to the spiritual guidance provided by pastors. Through a comprehensive analysis of biblical teachings and scholarly works by Wayne Grudem, Barry Van Wyk, and many others unveiling the expected unity among Christians within the Parish of Kumi Hospital, Diocese of Kumi. This study aims to shed light on God's original intent for unity in the body of Christ. The study comprehensively examines the distinct roles of apostles, prophets, evangelists, pastors, and teachers within the context of Kumi Hospital Parish. Through analyzing existing church leaders’ capacity, the research identifies obstacles and proposes practical recommendations to foster successful implementation. Conducted between November 2023 and May 2024, this study aims to enhance the effectiveness of the five-fold ministry concept within the parish. Hence, a literature review will be presented exploring the diverse perspectives on how these ministry roles contribute to spiritual development, unity, and growth, focusing on the context of Kumi Hospital Parish[ https://www.regent.edu/journal/journal.]. Showing scholars have highlighted various challenges, such as establishing effective leadership structures encompassing all five ministry roles and the lack of universally accepted definitions, leading to confusion in understanding each role's responsibilities. Showing, the difficulty in discerning and nurturing individuals with the appropriate gifts for each ministry role as it poses a significant obstacle. However, this paper aims to provide a comprehensive understanding of the complexities involved in implementing the five-fold ministry in Christian community development.
Undergraduate research